Sistem Pengendalian Mutu Pengolahan Udang Beku Melalui Prinsip Hazard Analisis Critical Control Point (HACCP) - Salma Salma; Budiman Budiman; Ilyas Ilyas (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Shrimp is a food ingredient that has perishable characteristics, so it requires proper handling to maintain product quality and safety. This study aims to understand the application of the quality system in frozen shrimp processing based on the principle of Hazard Analysis Critical Control Point (HACCP) at PT Dachan Mustika Aurora Tarakan. The research was carried out during the period from July to December 2024 with a qualitative descriptive approach. The results of the study show that the frozen shrimp processing system has followed the principles and stages of HACCP in general, starting from the receipt of raw materials, temperature checks, organoleptic tests, laboratory tests, processing with temperature control, washing, sorting, packaging, to storage in cold storage. However, there are still critical points at the Metal Detector washing and inspection stages, with the potential for significant danger in the form of metal chip contamination. The quality control process is carried out in layers to ensure that the final product meets national and international standards. The implementation of HACCP has consistently proven to be effective in improving food safety, maintaining the quality of frozen shrimp, and strengthening the competitiveness of products in the export market. These findings provide recommendations for the seafood processing industry to strengthen surveillance systems at critical points and improve personnel training to minimize the risk of contamination and ensure the sustainability of product quality.